Tax compliance measurement among taxpayers of UiTM Kedah staff / Daing Maruak bin Sadek ... [et al.] - Sadek, Daing Maruak; Anuar, Azyyati; Shamsul, Muhammad Zulhilmi; Abd Rahim, Mas Aida; Kasim, Noor Hidayah (UiTM Cawangan Kedah, 2022)
Malaysia has adopted the Self-Assessment Taxation System (SAS) since 2001 for corporate taxpayers and later introduced the system to businesses, partnerships and cooperatives, as well as individuals in 2003. However, according to many experts in taxation across the world, many countries including developing and developed ones, face difficulties in collecting tax payments from taxpayers effectively. Due to the implementation of a manual tax assessment and payment system, governments around the world are exposed to the increasing problems of tax losses. Therefore, this research addressed the influence of tax complexity and tax knowledge towards tax compliance among the taxpayers in a Malaysian setting, particularly the permanent staff of UiTM Kedah Branch. The data recorded from questionnaires were analysed using the Statistical Package for the Social Sciences (SPSS version 24). The results confirmed that tax complexity plays a significant role in determining tax compliance. However, tax compliance was not significantly influenced by tax knowledge. It can be concluded that further research should be undertaken to further comprehend the impacts of the present determinants within this study and other non-present ones towards Malaysian taxpayers’ compliance level.